2020
DOI: 10.1111/jocd.13338
|View full text |Cite
|
Sign up to set email alerts
|

Resistin adipokin in atopic dermatitis patients: A clinical, biochemical, and genetic study

Abstract: Background/Objectives Atopic dermatitis (AD) is an inflammatory chronic skin disorder. The etiology of AD is not fully understood. Therefore, we aimed by this study to shed light on the potential role of resistin in an etiopathogenesis of AD through investigation of resistin rs3745367 single nucleotide polymorphism (SNP) and resistin serum levels, and their relation to leukocytic count in a sample of Egyptian patients having atopic dermatitis. Methods This case‐control study included 45 patients having AD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…Banihani et al [41] found a significant reduction in resistin in a group of 75 AD patients (children and adults) when compared to the control group. Likewise, Farag et al [42] have found a decrease in resistin in a group of 45 Egyptian patients (adults and children; obese patients excluded), with an inverse correlation between blood resistin content and SCORAD score, which was also found in the present study. Based on the available data, it is possible to hypothesize that consistently lower levels of resistin coexist with increased severity of AD symptoms in adults.…”
Section: Potential Biomarkers Of Eczema Severitysupporting
confidence: 89%
“…Banihani et al [41] found a significant reduction in resistin in a group of 75 AD patients (children and adults) when compared to the control group. Likewise, Farag et al [42] have found a decrease in resistin in a group of 45 Egyptian patients (adults and children; obese patients excluded), with an inverse correlation between blood resistin content and SCORAD score, which was also found in the present study. Based on the available data, it is possible to hypothesize that consistently lower levels of resistin coexist with increased severity of AD symptoms in adults.…”
Section: Potential Biomarkers Of Eczema Severitysupporting
confidence: 89%
“…Adiponectin signaling enhances sebum secretion and subsequent protection of the skin against AD (Jung et al, 2017). It has also been shown that levels of other adipokines such as resistin and leptin affect the risk of AD (Banihani et al, 2018;Farag et al, 2020;Jaworek & Szepietowski, 2020;Kovács et al, 2020;Seo & Seong, 2019). Thus, a considerable amount of literature supports the role of adipokines in AD disease.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin and resistin have been found to be inversely correlated to the intensity of eczema in adult patients compared with healthy subjects, thus being considered as promising biomarkers in the disease [ 68 , 69 ]. Specifically, the resistin rs3745367 gene polymorphism could contribute to the development of AD according to gender and age [ 69 , 70 ]. Surprisingly, Machura et al (2013) found higher levels of serum resistin in AD children (especially in boys) compared with healthy controls.…”
Section: Role Of Obesity In Admentioning
confidence: 99%